Effect of Kefir on Soybean Isoflavone Aglycone Content in Soymilk Kefir - Yang, Minke; Yang, Xiaojuan; Chen, Xiaoqu; Wang, Jie; Liao, Zhenlin; Wang, Li; Zhong, Qingping; Fang, Xiang (Frontiers in Nutrition, 2020)
Kefir is traditional fermented milk originating from Caucasus area and some other parts of Eastern Europe. In this study, the kefir culture, which is modified upon the addition of lactic acid bacteria (LAB) cells, specifically for soymilk kefir fermentation with the highest capacity of isoflavones biotransformation were successfully built, and the metagenomics composition of soymilk or milk fermented using these kefir culture were investigated. Here, the metagenome analysis showed that the microbiota of kefir among M-K (milk were inoculated kefir), SM-K (soymilk and equal volume milk were inoculated kefir) and S-K (pure milk were inoculated kefir) were related to the addition of soymilk or not. Furthermore, the HPLC chromatogram revealed that Guixia 2 (Guangzhou, China) may be a good source for soymilk kefir fermentation due to its highest isoflavone aglycones content (90.23±1.26 μg/g in daidzein, 68.20±0.74 μg/g in genistein). Importantly, the starter culture built by adding of 1.5 g Probiotics (Biostime, Guangzhou, China) to Chinese kefir showed a significant increase on the levels of isoflavone aglycones(72.07±0.53 μg/g in isoflavone aglycones). These results provided insights to understand the suitable soybean cultivar and starter cultures, which exhibit promising results of isoflavone biotransformation and flavor promotion during soymilk kefir fermentation.